MENINGKATKAN KEMAMPUAN HITUNG PERBANDINGAN MELALUI MEDIA FLOWCHART PADA SISWA KELAS V SDN KLUMPIT 03 KEC. SOKO-TUBAN - Sumijan, - (Universitas Pendidikan Indonesia, 2016)
Abstract: Mathematics is one of the basic sciences taught at all levels of schooling, with the aim to prepare students to be able to confront changing circumstances in life and in the world is always evolving, through acting on the basis of logical thinking, rational, critical, careful, honest, effectively and efficiently and can use matmatika and mindset of mathematics in daily life - today and in studying various sciences. This research uses classroom action research with the object of Action